Perancangan Program Pemesanan (JAI) Jahit Andalan Indonesia Pada PT. Jahit Andalan Indonesia - Baharudin Mulya; Popon Handayani (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Technology today is growing so rapidly, especially in the field of information technology. This is a natural thing for people who live in today's technological era. So that they have to keep up with developments, both at work and in carrying out daily activities, they rely heavily on technologies that can facilitate, speed up and complete the activities being carried out. In companies engaged in the industry, especially sewing services, it is still carried out with notes and there are no reports per period, and every sewing transaction comes to the store. By conducting this research, it is hoped that a website-based sales media will be created that can provide convenience for customers in finding available sewing information and sewing order data management information.